Standards in Neurological Rehabilitation, June 1997 - Michael P. Barnes; European Federation of Neurological Societies Task Force (Behavioural Neurology)
The European Federation of Neurological Societies (EFNS) Scientific Panel on Neurorehabilitation established a Task Force on standards in neurological rehabilitation in June 1996. The remit for the Task Force was to: (1) produce a report on the state of neurological rehabilitation across Europe; and (2) recommend standards for the provision of neurological services for disabled people. The main conclusions of the Task Force were as follows: (1) A questionnaire circulated to each European member country has indicated a significant lack of adequate neurological rehabilitation facilities across Europe. Very few countries have any established network of neurological rehabilitation centres. Few countries have adequately trained neurological rehabilitation physicians, therapists or nurses. Such poor facilities should be seen in the context of the large numbers and increasing prevalence of people with neurological disabilities. (2) The Task Force has summarized the significant benefits that can follow from the establishment of a dedicated and cost effective neurological rehabilitation service including functional improvement, reduction of unnecessary complications, better coordination and use of limited resources, improved opportunities for education, training and research and a clear point of contact for the disabled person. (3) The Task Force recommends minimum standards for the prevention of neurological disability including access to health education, genetic counselling and emergency resources. The Task Force also encourages governments to invest in improved legislation for accident prevention. (4) The Task Force has outlined some minimum standards for the staffing of a neurological rehabilitation service including improved training both for neurologists and rehabilitation physicians. Such training could include a cross-national training programme both for physicians and other health care staff. (5) The Task Force supports a two-tier system of neurological services. We believe that disabled individuals should have access to a regional specialist service as well as a local community service. The regional specialist service would cater for people with more complicated and severe disabilities, including spinal injury and severe brain injury. The regional centres would provide specialist expertise for wheelchairs and special seating, orthotics, continence and urological services, aids and equipment including communication aids and environmental controls, prosthetics and driving assessment. The Task Force additionally endorses the development of local and community based rehabilitation teams with clear links to the regional centre. (6) The Task Force recognizes the limited amount of rehabilitation research and encourages individuals, universities and governments to invest more in rehabilitation research. Such investment should produce benefits for disabled people and their carers and in the long term benefits for the national economy. (7) The Task Force realizes that neurological rehabilitation is poorly developed both in Europe and the world as a whole. We firmly endorse international co-operation in this field and are happy to co-operate with any international organization in order to develop such links for clinical, educational or research initiatives. (8) The Task Force encourages individual countries to produce a document summarizing their own situation with regard to these standards and to produce a timetable for action to improve their situation. The EFNS Task Force would be pleased to assist in the publication of such deliberations or to act as a focus for international education and research or for sharing of examples of good practice.